The growth capability of natural and mutated bacteria in a solid nutrient-contaminated medium with lead and cadmium - Aljanabi, Huda A. Yaseen; Al-Jaberi, Meiad M. (Edelweiss Applied Science and Technology, 2025)
This study investigated the growth of natural and mutated bacterial strains (B. subtilis and P. fluorescens) in nutrient agar contaminated with heavy metals (lead and cadmium). The results showed significant differences (p≤0.01) in bacterial counts for the various treatments. B. subtilis natural outperformed P. fluorescens natural in unpolluted medium, but in lead-contaminated medium, B. subtilis also showed better growth. In contrast, P. fluorescens had a higher count than B. subtilis in cadmium-contaminated medium. Mutagenesis of B. subtilis for 30 minutes led to a significant increase in growth across all media, while 60-minute mutations resulted in reduced growth, particularly under heavy metal stress. For P. fluorescens, 30-minute mutations showed improved growth in lead-contaminated medium compared to the natural strain, while 60-minute mutations also performed well in cadmium-contaminated medium. The findings suggest that mutation can enhance bacterial resistance and tolerance to heavy metals, likely due to changes in DNA and protein structures. These adaptations may involve mechanisms like ion efflux, bioaccumulation, and biotransformation, contributing to the bacteria’s ability to survive in contaminated environments. These results highlight the potential of using mutated bacteria for the bioremediation of heavy metal-polluted environments.